Evaluating Microcredit: Effects of the 5Cs of Credit Analysis and Entrepreneur Characteristics on Loan Performance among MSMEs in Yogyakarta - Joenoes, Kartini Sally Hb; Sugiyanto, Catur; Sukamdi, Sukamdi; Moeljono, Djokosantoso (Asian Journal of Social and Humanities, 2025)
Micro, small, and medium enterprises (MSMEs) have a significant role in the national economy, creating jobs opportunities, increasing Gross Domestic Product (GDP), and promoting credit stability during times of crisis. However, MSMEs frequently face obstacles when attempting to access financial resources. Although the Indonesia government has implemented several measures to support MSMEs, such as the credit relaxation policy, the risk of loan non-performance loan remains tangible. This study seeks to identify the dominant factors underpinning MSMEs' failure to repay their loans focusing on 5Cs of credit analysis and characteristics of individual entrepreneurs. This study finds that the principles identified in the 5Cs of credit analysis are significantly and negatively correlated with non-performing loans, while the characteristics of individual entrepreneurs is not significantly correlated. Of the 5Cs of credit analysis, capacity and collateral are identified as the most determinant factors behind non-performing loans, though this finding differs from those of several previous studies. Meanwhile this study provides important insight which will enable the banking industry and policymakers to mitigate the credit risks experienced by MSMEs and promote the future sustainability of this sector.